The effect of substrate temperature on the optical properties of SnSb4S7 thin films. (January 2015) - Jebali, A.; Rabeh, M. Ben; Khemiri, N.; Kanzari, M.
Graphical abstract: Highlights: XRD suggest that SnSb4 S7 crystallized into monoclinic structure with a ( 2 1 ¯ 3 ) plane. SnSb4 S7 films have absorption coefficients between 104 and 105 cm-1 in the visible. SnSb4 S7 samples have direct band gap in the range 1.45–1.80 eV. Abstract: In this work, SnSb4 S7 thin films were prepared by vacuum evaporation method, and the effect of substrate temperature on the structural and optical properties were investigated. Substrate temperature was varied from room temperature to 170 °C. Optical constants such as band gap, absorption coefficient, extinction coefficient, refractive index, and dielectric constant were determined from the measured transmittance and reflectance spectra in the wavelength range between 300 and 1800 nm using the envelope method. The dispersion behavior of the refractive index was studied in terms of the single-oscillator Wemple–DiDomenico (W–D) model, and the physical parameters of the refractive index dispersion and the dispersion energy were found. The electrical free carrier susceptibility and the carrier concentration of the effective mass ratio were estimated according to the Spitzer–Fan model. Furthermore, the optical band gap values were calculated by the W–D model and the Tauc model, respectively. The major result of this study is optical, structural, and dielectric properties of SnSb4 S7 could be modified with the different substrate temperature.